2020
DOI: 10.1088/1674-1056/ab5fc0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of system–reservoir correlations on temperature estimation*

Abstract: In many previous temperature estimation schemes, the temperature of a sample is directly read out from the final steady state of a quantum probe, which is coupled to the sample. However, in these studies, information of correlations between system (the probe) and reservoir (the sample) is usually eliminated, leading the steady state of the probe is a canonical equilibrium state with respect solely to system’s Hamiltonian. To explore the influence of system–reservoir correlations on the estimation precision, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Under such treatment, one can see the frequency shift Ω → Ω shall lead to a smaller value of gg (∞)/ ee (∞) [see Figs. 4(a) and 5(a)] compared with that of the canonical Gibbs state case, which implies the breakdown of canonical statistics [62][63][64]. Moreover, if Ω > Ω * , the frequency renormalization results in a larger QFI in comparison with that of the canonical statistics [see Fig.…”
Section: B Breakdown Of the Canonical Statisticsmentioning
confidence: 99%
“…Under such treatment, one can see the frequency shift Ω → Ω shall lead to a smaller value of gg (∞)/ ee (∞) [see Figs. 4(a) and 5(a)] compared with that of the canonical Gibbs state case, which implies the breakdown of canonical statistics [62][63][64]. Moreover, if Ω > Ω * , the frequency renormalization results in a larger QFI in comparison with that of the canonical statistics [see Fig.…”
Section: B Breakdown Of the Canonical Statisticsmentioning
confidence: 99%
“…At present, many schemes have been proposed to improve the estimation precision of the temperature with quantum estimation theory, such as a ring-structure system interacting with the bath, [40] twolevel atoms transported through an optical cavity, [41] a uniformly accelerated two-level atom coupled to a massless scalar field in the Minkowski vacuum, [42] and the probe system embedded into the structured reservoir. [43][44][45][46][47] However, the model that the two-level system (qubit) is directly immersed in a ther-mal reservoir has not been utilized for the temperature estimation. In addition, several researchers have reported that the squeezed state or reservoir has the potential to protect the nonclassical effects of the quantum system [48] and improve the accuracy of phase estimation.…”
Section: Introductionmentioning
confidence: 99%